Criterios e indicadores para la formulación de un obsevatorio de desarrollo territorial de las relaciones entre agua, agricultura y paisaje - Valenzuela Montes, Luis Miguel; Matarán Ruiz, Alberto (Observatorio Medioambiental, 2007)
This article presents an «objective-model» of a Spatial Development Observatory of the relationships between water, agricultura and landscape. This is based on the new principles and models on spatial planning coming from the «European Spatial Strategy» (EC, 1999), the principles of the «New Water Culture», and the increasing interest on designing and applying indicator systems as a tool to assess environmental processes. The main contributions related to the stablishment of objectives, criteria and functions of the Observatory, and to the set of indicators provided to describe the key factors according to the relationship between water and territory. The development of new tools like the described one is essential for an effective implementation of the information provided for the decision making process. It is also very usefull to innovate in the gobernance, participation and integration between sectoral planning (hydrologic) and spatial planning